Serum zonulin, brain-derived neurotrophic factor, and oxidative stress levels in individuals using paper (A4) impregnated with synthetic cannabinoids - Kulaksızoğlu, Sibel; Erdoğan, Ali; Tosun, Oğuzhan; Görgülü, Zeynep Yaren; Acar, Esra; Kireç, Yavuz; Karabulut, Sercan; Kulaksızoğlu, Burak; Cinemre, Buket; Metin, Özmen (Frontiers in Psychiatry, 2025)
IntroductionA4 is paper impregnated with synthetic cannabinoids, used as a novel psychoactive substance. The aim of this study was to investigate serum zonulin, brain-derived neurotrophic factor (BDNF), total oxidant status (TOS), total antioxidant status (TAS) and oxidative stress index (OSI) in patients predominantly using synthetic cannabinoid-impregnated papers.MethodsThirty patients with A4 use and 30 healthy volunteers (HC) were included. Peripheral blood was collected for zonulin, BDNF, TOS, TAS and OSI levels after 8–12 hours of fasting. Substance Craving Scale (SCS) was administered to the patient group.ResultsPatients using A4 had lower BDNF levels (p=0.001) and higher TOS and OSI levels (p<0.001, p<0.001) compared to HC. Zonulin and TAS levels of both groups were similar (p>0.005 for both). No correlation was found between the SCS scores and zonulin, BDNF, TAS, TOS and OSI values (p>0.05 for all). When ROC analysis was performed, the cut-off value for BDNF in the patient group was ≤2.51 pg/mL, sensitivity was 66.7%, specificity was 63.3%, PPV was 76.0%, NPV was 76.0%, and area under the ROC curve was 0.744. The cut-off value for TOS was ≥14.51 μmol/L, sensitivity 70.0%, specificity 66.7%, PPV 77.7%, NPV 79.5%, area under the ROC curve 0.766. The cut-off value for OSI was ≥0.69, sensitivity 76.7%, specificity 63.3%, PPV 76.0%, NPV 81.3%, area under the ROC curve 0.773.DiscussionThe findings suggest that A4 use may impair neuroplasticity and disrupt oxidative stress balance. BDNF, TOS, and OSI appear to be promising biomarker candidates for identifying individuals with A4 use.